(untitled) (Journal of Hama University, 2024)
This study was conducted on (150) birds from one of the commercial crosses of broiler chickens, and it aimed to study the effect of adding different percentages of Nano-selenium and organic selenium on some serum proteins in broiler chickens exposed to oxidative stress. Six groups were used, with an average of (25) birds in each group. The study groups were fed a balanced fodder mixture in terms of energy and protein, and the control group G1 ate water only, while hydrogen peroxide was added to the drinking water at a rate of (0.5)%/ liter at the age of 15 days in the G2 group 8 Hours daily for 10 days, and the G3 group added Nano-selenium at a concentration of (0.07) mg/ kg of feed + hydrogen peroxide in drinking water at a rate of (0.5)% /liter 8 Hours daily for 10 days, group G4 added Nano-selenium at a concentration of (0.15) mg / kg of feed + hydrogen peroxide in drinking water at a rate of (0.5)% /liter 8 Hours daily for 10 days, group G5 added organic selenium at a concentration of (0.07) mg / kg of feed + hydrogen peroxide in drinking water at a rate of (0.5)% /liter 8 Hours daily for 10 days, groups G6 added organic selenium at a concentration of (0.15) mg / kg of feed + hydrogen peroxide in drinking water at a rate of (0.5)% /liter 8 Hours daily for 10 days. The experiment continued from 15 days old to 45 days . The results of the statistical analysis showed that the addition of Nano selenium and organic selenium led to a significant increase (P≤0.05) in the level of total protein, albumin and globulin in the groups of nanoselenium and organic selenium at the age of 40.35 days compared with the control group G2. The study also showed that there were no significant differences (P≤0.05) in the levels of total protein, albumin, and globulin in the nanoselenium supplementation groups, compared with the organic selenium groups, at the age of 35 and 40 days.